2.5D elastic wave propagation in non-homogeneous media coupling the BEM and MLPG methods. (April 2015) - Tadeu, A.; Stanak, P.; Antonio, J.; Sladek, J.; Sladek, V.
Abstract: This paper describes a 2.5D numerical frequency domain model based on the mutual coupling of the boundary element method (BEM) and the meshless local Petrov–Galerkin (MLPG) method for simulating elastic wave propagation in non-homogeneous media, when the geometry does not change in the z direction. The BEM is used to model the propagation within the unbounded homogeneous domain while the MLPG is used to simulate the confined non-homogeneous domains. The coupling of the two numerical techniques is accomplished directly at the nodal points located at the common interface. Continuity of mechanical displacements and tractions at the interface is imposed through the collocation of continuity equations on the interface with use of the moving least-squares (MLS) scheme. The MLS was also chosen for the approximation of the trial functions for the MLPG formulation. The coupled BEM–MLPG approach is verified against the results provided by an analytical solution developed for a circular multi-layered subdomain, in which the elastic material properties within the circular non-homogeneous region are assumed to vary in the radial direction. Finally, an unbounded medium containing two non-homogeneous inclusions excited by a blast load is used to illustrate the applicability of the proposed model.